The Effectiveness of Mirror Therapy on Stroke Patients: Literature Review - Dwi Ulfah Kamaliyah; Ramona Kesya Darmawan; Dini Nur Alpiah (Publikasi Indonesia, 2024)
Stroke is a disease that attacks the nervous system due to loss of blood supply to the brain and causes interference in carrying out daily activities with a prevalence of 10.9% in Indonesia. Stroke on average affects people aged 56 years. Mirror therapy is a therapeutic exercise that involves moving the body while observing the unaffected part to provide visual stimulation to the brain. The approach used in this study is a literature review or Literature Review. This study used a literature review approach, using a PICO search in various databases including Pubmed, Google Scholar, and Science Direct. 5 journals met the criteria and showed the results that Mirror Therapy performed once a day for 15-50 minutes lasting for 2 months with a p-value <0.005 showed a significant impact in improving muscle and motor function of stroke patients. It can be concluded that mirror therapy is effective in strengthening muscles and can facilitate the recovery of motor function in stroke patients.